2022
DOI: 10.3389/fgene.2022.972990
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation mechanism of flavonoids biosynthesis gene during fruit development in astragalus membranaceus

Abstract: Astragalus membranaceus, as an important medicinal plant, are an excellent source of flavonoids. Flavonoid compounds in A. membranaceus have been widely used in medicine and supplement, but known of the molecular mechanism of flavonoid biosynthesis is still very few. Here, we analyzed the association between flavonoid content and gene expression pattern during six different fruit developmental stages. Sixteen gene expression trends were significantly identified, involving 8,218 genes. The gene expression trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Transcription factors play a crucial role in regulating the active expression of synthetases, with the transcriptional activation of synthetic factors being a key regulatory mechanism in the plant secondary metabolism [62,63]. Numerous studies have identified various families of transcription factors (MYB, MYC(bHLH), bZIP, and WD40) involved in the biosynthesis of flavonoids in medicinal plants like dendrobium [24], astragalus [64], sea buckthorn [65], and jujube [66]. In this study, it was observed that transcription factors such as MYB, bHLH, and bZIP, known to regulate flavonoid biosynthesis, were also present in the WR and RR of P. kingianum Coll.et Hemsl..…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors play a crucial role in regulating the active expression of synthetases, with the transcriptional activation of synthetic factors being a key regulatory mechanism in the plant secondary metabolism [62,63]. Numerous studies have identified various families of transcription factors (MYB, MYC(bHLH), bZIP, and WD40) involved in the biosynthesis of flavonoids in medicinal plants like dendrobium [24], astragalus [64], sea buckthorn [65], and jujube [66]. In this study, it was observed that transcription factors such as MYB, bHLH, and bZIP, known to regulate flavonoid biosynthesis, were also present in the WR and RR of P. kingianum Coll.et Hemsl..…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid biosynthesis is a complicated and volatile process involving a series of enzymes, including phenylalanine ammonia lyase (PAL), cinnamate-4-hydroxylase (C4H), 4-coumaroyl CoA ligase (4CL), chalcone synthase (CHS), chalcone isomerase (CHI), flavonoid synthase (FLS), and flavonoid 3-hydroxylase (F3'H) [39]. PAL, C4H, and 4CL enzymes are important regulators in the synthesis of the phenylpropane metabolic pathway [86]. In this research, four PAL, one C4H, and fourteen 4CL DEGs were identified from the transcriptome data.…”
Section: Effect Of Uv-b Radiation On Flavonoid Biosynthesismentioning
confidence: 99%
“…In recent years, flavonoid biosynthesis genes, expressed by many plants, have been extensively studied; these have included Arabidopsis thaliana [25], Camellia sinensis [26], and Carthamus tinctorius L. [27]. Specifically, the transcriptional regulatory mechanism of flavonoids during fruit development [28] and the response mechanism under drought [29] and salt-alkali stress [30] in A. mongholicus have been studied. However, the effect of cutting on the content of flavonoids in this species is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%